2021
DOI: 10.1093/ehjci/jeab208
|View full text |Cite
|
Sign up to set email alerts
|

Visual echocardiographic scoring system of the left ventricular filling pressure and outcomes of heart failure with preserved ejection fraction

Abstract: Aims Elevated left ventricular filling pressure (LVFP) is a powerful indicator of worsening clinical outcomes in heart failure with preserved ejection fraction (HFpEF); however, detection of elevated LVFP is often challenging. This study aimed to determine the association between the newly proposed echocardiographic LVFP parameter, visually assessed time difference between the mitral valve and tricuspid valve opening (VMT) score, and clinical outcomes of HFpEF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
(62 reference statements)
2
11
0
Order By: Relevance
“…Moreover, the VMT score ≥2 was confirmed to be correlated with the prognosis of HFpEF population 13 These gave evidence to the results in our study, which revealed that the VMT score ≥2 was associated with elevated risk of 1-year all-cause and the VMT score of 3 was correlated with increased risk of CVD-cause mortality.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, the VMT score ≥2 was confirmed to be correlated with the prognosis of HFpEF population 13 These gave evidence to the results in our study, which revealed that the VMT score ≥2 was associated with elevated risk of 1-year all-cause and the VMT score of 3 was correlated with increased risk of CVD-cause mortality.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, the visually assessed time difference between the mitral valve (MV) and tricuspid valve (TV) opening (VMT), combined with an indicator of right atrial pressure [inferior vena cava (IVC) dimension], formed the VMT score 12 . The VMT score was reported to be correlated with the increase of left ventricular filling pressure (LVFP), 12 and served as a useful indicator for evaluating the prognosis of HFpEF 13 . Thus, we suspected that the VMT score might be a valuable prognostic biomarker for HFmrEF patients.…”
Section: Introductionmentioning
confidence: 99%
“…This retrospective observational study examined the association between the amount of VAT and SAT and clinical outcomes in Japanese patients with HFpEF. Some participant data from this study were previously published [7] , [19] , [20] , [21] , [22] , [23] , but not in relation to the prognostic value of adiposity. Patients presenting at Gunma University Hospital in Maebashi, Japan between January 2014 and December 2020 were screened for HFpEF.…”
Section: Methodsmentioning
confidence: 97%
“…In this edition of the journal, the same group has applied the VMT score retrospectively on 310 HFpEF patients and evaluated cardiac death and heart failure hospitalization after 2 years as primary outcome. 13 Patients with VMT ≥2 had worse outcome, and the VMT score still showed incremental value also after adjusting for other variables. Patients with VMT ≥2 showed more signs of poor function and were thus sicker, which is consistent with their previous study that patients meeting this cut-off truly have a high filling pressure.…”
mentioning
confidence: 85%
“…Patients with VMT ≥2 showed more signs of poor function and were thus sicker, which is consistent with their previous study that patients meeting this cut-off truly have a high filling pressure. Notably, both the previous 6 and the new study 13 showed that VMT score performed well to stratify patients with atrial fibrillation. This is interesting because these patients tend to have monophasic LV inflow, which makes use of conventional LV filling pressure parameters problematic.…”
mentioning
confidence: 92%